Is there a difference in utilization of a perioperative treatment approach for gastric cancer between safety net hospitals and tertiary referral centers?. Issue 4 (1st June 2021) - Turgeon, Michael K.; Lee, Rachel M.; Keilson, Jessica M.; Ju, Michelle R.; Porembka, Matthew R.; Alterio, Rodrigo E.; Kronenfeld, Joshua; Datta, Jashodeep; Goel, Neha; Wang, Annie; Lee, Ann Y.; Fernandez, Manuel; et al.
Abstract : Background and Objectives: Perioperative therapy is a favored treatment strategy for gastric cancer. We sought to assess utilization of this approach at safety net hospitals (SNH) and tertiary referral centers (TRC). Materials and Methods: Patients in the US Safety Net Collaborative (2012–2014) with resectable gastric cancer across five SNH and their sister TRC were included. Primary outcomes were receipt of neoadjuvant chemotherapy (NAC) and perioperative therapy. Results: Of 284 patients, 36% and 64% received care at SNH and TRC. The distribution of Stage II/III resectable disease was similar across facilities. Receipt of NAC at SNH and TRC was similar (56% vs. 46%, p = 0.27). Compared with overall clinical stage, 38% and 36% were pathologically downstaged at SNH and TRC, respectively. Among patients who received NAC, those who also received adjuvant chemotherapy at SNH and TRC were similar (66% vs. 60%, p = 0.50). Asian race and higher clinical stage were associated with receipt of perioperative therapy (both p < 0.05) while treatment facility type was not. Conclusions: There was no difference in utilization of a perioperative treatment strategy between facility types for patients with gastric cancer. Pathologic downstaging from NAC was similar across treatment facilities, suggesting similar quality and duration of therapy. Treatment at an SNH is not a barrier to receiving standard‐of‐care perioperative therapy for gastric cancer.